Association between road traffic accidents and drugs belonging to the antiseizure medications class: A pharmacovigilance analysis in VigiBase - Chrétien, Basile; Nguyen, Sophie; Dolladille, Charles; Morice, Pierre‐Marie; Heraudeau, Marie; Loilier, Magalie; Fédrizzi, Sophie; Bourgine, Joanna; Cesbron, Alexandre; Alexandre, Joachim; Bocca, Marie‐Laure; Fréret, Thomas; et al. (British Journal of Clinical Pharmacology, 2022)
AIMS: Due to their central mechanism of action, antiseizure medications (ASMs) could lead to adverse effects likely to impair driving skills. Their extended use to neuropsychiatric disorders makes it a class of drugs to monitor for their road traffic accidental (RTA) potential. We aimed to assess the reporting association between ASMs and RTAs using the World Health Organization pharmacovigilance database (VigiBase). METHODS: We performed a disproportionality analysis to compute adjusted reporting odds ratios to evaluate the strength of reporting association between ASMs and RTAs. A univariate analysis using the reporting odds-ratio was used to assess drug-drug interactions between ASMs and RTAs. RESULTS: There were 1 341 509 reports associated with at least 1 ASM in VigiBase of whom 2.91‰ were RTAs reports. Eight ASMs were associated with higher reporting of RTAs compared to others (ranging from 1.35 [95% confidence interval 1.11-1.64] for lamotrigine to 4.36 [95% confidence interval 3.56-5.32] for cannabis). Eight significant drug-drug interactions were found between ASMs and the onset of RTA, mainly involving CYP450 induction. CONCLUSION: A significant safety signal between RTAs and some ASMs was identified. Association of several ASMs might further increase the occurrence of RTA. ASMs prescription in patients with identified risk factors of RTA should be considered with caution. Study number: ClinicalTrials.gov, NCT04480996.